Laparoscopic Resection of an Intra-Abdominal Esophageal Duplication Cyst: A Case Report and Literature Review. (26th March 2015) - Watanobe, Ikuo; Ito, Yuzuru; Akimoto, Eigo; Sekine, Yuuki; Haruyama, Yurie; Amemiya, Kota; Kawano, Fumihiro; Fujita, Shohei; Omori, Satoshi; Miyano, Shozo; Kosaka, Taijiro; Machida, Michio; et al.
Abstract : Duplication of the alimentary tract is a rare congenital malformation that occurs most often in the abdominal region, whereas esophageal duplication cyst develops typically in the thoracic region but occasionally in the neck and abdominal regions. Esophageal duplication cyst is usually diagnosed in early childhood because of symptoms related to bleeding, infection, and displacement of tissue surrounding the lesion. We recently encountered a rare adult case of esophageal duplication cyst in the abdominal esophagus. A 50-year-old man underwent gastroscopy, endoscopic ultrasonography, computed tomography, and magnetic resonance imaging to investigate epigastric pain and dysphagia that started 3 months earlier. Imaging findings suggested esophageal duplication cyst, and the patient underwent laparoscopic resection followed by intraoperative esophagoscopy to reconstruct the esophagus safely and effectively. Histopathological examination of the resected specimen revealed two layers of smooth muscle in the cystic wall, confirming the diagnosis of esophageal duplication cyst.